CO, CO2, and SO2 detection based on functionalized graphene nanoribbons: First principles study - Ehab Salih (17075206) (2020)
In this study, density functional theory (DFT) has been used to build armchair graphene nanoribbon (AGNR) gas sensor and study its capacity to detect carbon monoxide (CO), carbon dioxide (CO2), and sulfur dioxide (SO2) gases. The adsorption of these gases on AGNR was confirmed based on the adsorption energy (Eads), adsorption distance (D), charge transfer (ΔQ), density of states (DOS), and band structure. In order to improve the adsorption capacity, three different modified AGNR systems have been built. AGNR was first functionalized with epoxy (-O-) group (AGNR-O), then with hydroxyl (-OH) group (AGNR-OH), and finally with (-O-) along with (-OH) groups (AGNR-O-OH). Before modification, the adsorption energies have been found to be −0.260, −0.145, and −0.196 eV due to the adsorption of CO, CO2, and SO2, respectively. After modification, the adsorption energy increased remarkably to −0.538 and −0.767 eV for the cases of AGNR-O-OH-CO2 and AGNR-O-OH-SO2, respectively. Indicating that functionalizing the surface of AGNR can improve significantly its performance for the field of gas sensing. Other Information Published in: Physica E: Low-dimensional Systems and Nanostructures License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.physe.2020.114220